Putative effect of light intensity to reproduction in blue foxes - Rekila Teppo; Korhonen, Hannu.T.; Koskinen, Nita; Sepponen, Juhani; Pylkkö, Päivi (Rus, 2005)
Majority of blue foxes in Finland are housed in traditional shed houses. The shed house usually has nontransparent roofs against sunlight. Increasing daylight and intensity of light during spring is a key factor in stimulating reproduction. Despite of long lasted selection for reproductive success the number of nonreproducing females is however high. Could the explanation for this be that nontransparent roofs serve as a hindrance to the sunlight and therefore affect to the total light intensity. Light intensity was measured from January to May in a traditional shed house with a nontransparent roof. A rearing hall with the 30% light transpiring roof was used as a reference. Total 50 primiparous blue fox female siblings were randomly allocated in the shed house and in the rearing hall. The blue fox vixens were artificially inseminated. The highest light intensity was detected four weeks earlier in the shed house than in the rearing hall (Figs 1 and 2). After the light intensity peaked outside it decreased in the shed house but stayed at high level in the rearing hall. The number of inseminated females was higher in the hall than in the shed house (47 vs. 37, P<0.001, respectively). This difference in the number of inseminated females is probably due to high light intensity enough for females to reach estrus. The light intensity in the rearing hall resembles the light intensity in a natural environment. However, in the shed house the light intensity first increased and then decreased. Little is known about sufficient light intensity needed for a good reproduction result in blue foxes. However, practical experience is that 100 lux is the lowest dose of light needed for estrus. Light intensity below 100 lux was detected in the shed house (Fig 2). Blue foxes females are naturally adjusted to increasing daylight hours and light intensity in the spring rather than first rapidly increasing and then rapidly decreasing light intensity. It probably would be worthwhile to study whether the light intensity fluctuation correlates to the number of nonreproducing females
Keywords: ko; turkiseläimet; sinikettu; lisääntyminen; valo